The effect of interaction between Melanocortin-4 receptor polymorphism and dietary factors on the risk of metabolic syndrome. Issue 1 (December 2016) - Koochakpoor, Gelareh; Daneshpour, Maryam; Mirmiran, Parvin; Hosseini, Seyed; Hosseini-Esfahani, Firoozeh; Sedaghatikhayat, Bahareh; Azizi, Fereidoun
Abstract Background Controversial data is available on the effect of the Melanocortin-4 receptor (MC4R) gene variation on metabolic syndrome (MetS) and ineffectiveness of diet in managing MetS. Effects of the interaction between MC4R polymorphism and dietary factors on MetS were investigated in this study. Methods Subjects of this nested case-control study were selected from among participants of Tehran Lipid and Glucose Study. Each case (n  = 815) was pair matched randomly with a control by age (±5 years) and sex from among those who had not developed ≥1 MetS components at the time that the corresponding case developed MetS. Dietary patterns were determined using factor analysis on 25 foods groups using a valid and reliable, 168-item semi-quantitative food frequency questionnaire (FFQ). MC4R rs12970134 were genotyped by Tetra-Primer ARMS-polymerase chain reaction analysis. Adjusted conditional logistic regression was used to estimate the interactions of SNP with quartiles of dietary factors in relation to MetS. MetS was defined by the modified National Cholesterol Education Program/Adult Treatment panel III. Results Two dietary patterns were extracted. The healthy dietary pattern was loaded heavily on vegetables, legumes, low fat dairy, whole grains, liquid oils and fruits; the western dietary pattern consisted of a high intake of soft drinks, fast foods, sweets, solid oils, red meats, salty snacks, refined grains, high fat dairy, tea and coffee, eggs and poultry. Among A allele carriers, being in the highest quartiles of western dietary pattern score and saturated fatty acid intake had an increased risk of MetS, compared to those in the lowest quartile (P trend = 0.007). Saturated fatty acid intake could modulate the association of A allele carriers of MC4R with MetS (P interaction = 0.03). A significant interaction was observed between rs12970134 with total fat and iron intake on the risk of abdominal obesity (P interaction < 0.05). Conclusion Our findings suggest an interaction between rs12970134 and western dietary pattern, fat and vegetable intakes on the risk of MetS or its components.